Penggunaan Serbuk Batu Bata Merah Sebagai Filler Campuran Aspal AC-WC, Pengganti Semen dan Abu Batu dengan Marshall Test - Poerwodihardjo, F. Eddy; Hudoyo, Citra Pradipta (Universitas Nahdlatul Ulama Blitar, 2024)
Asphalt concrete as a material for road construction has long been known and widely used in road construction. This study aims to determine the effect of using red brick powder as a filler in the AC-WC asphalt mixture compared to cement and stone ash using the Marshall test with filler variations of 1%, 2%, 3%, and 4%. The determination of the optimum asphalt content was done with trial mixes of 60/70 penetration asphalt starting at asphalt contents of 5.5%, 6%, 6.5%, 7%, and 7.5%. From the initial asphalt mixture tests, an Optimum Asphalt Content (OAC) of 7% was obtained, which meets the Bina Marga 2018 specifications. The results of the Marshall tests on variations of red brick powder, cement, and stone ash fillers at 1% and 2% filler content did not meet the Bina Marga 2018 specifications. However, at 3% and 4% filler content, all Marshall test results met the Bina Marga 2018 specifications. The optimum value of the AC-WC asphalt mixture obtained from the Marshall test was with 4% cement filler, yielding a VIM of 4.239%, VMA of 17.305%, VFA of 79.880%, Marshall stability of 1551 kg, flow of 3.23 mm, and MQ of 480 kg/mm. The use of red brick powder as a filler at 4% filler content was better than stone ash and can be used as it approaches the optimum value, with a VIM of 4.267%, VMA of 17.226%, VFA of 79.637%, Marshall stability of 1529 kg, flow of 3.20 mm, and MQ of 478 kg/mm.